Multicenter review of a tadalafil suspension formulation for infants and children with pulmonary hypertension: A North American experience - David Edward Youssef; Stephanie S. Handler; Susan Marjorie Richards; Catherine Anne Sheppard; Jenna Smith; Kathryn Tillman; Matthew Pietrosanu; Edward Kirkpatrick; Angela Bates; Angela Bates (Frontiers Media S.A., 2023)
IntroductionPhosphodiesterase type 5 (PDE5) inhibitors, with sildenafil the earliest among them, are widely used in the management of pediatric pulmonary arterial hypertension (PAH). Tadalafil is a PDE5 inhibitor with a long half life (16 h), stable pharmacokinetics and pharmacodynamics, and minimal adverse effects. However, the utility of tadalafil suspensions in this setting has not been widely explored due to a lack of clinical experience. We present a multicenter experience that details the safety and tolerability of a tadalafil suspension, either alone or in combination with another vasodilator, for the management of pediatric pulmonary hypertension (PH).Methods and materialsThis is a retrospective chart review of infants and children at Children's Wisconsin and the Stollery Children's Hospital enrolled in pediatric PH programs between December 2013 and April 2022 managed with a tadalafil suspension. Patients aged six years of age and under who were treated with a tadalafil suspension were included. Demographics, clinical information, echocardiographic and hemodynamic measurements, and laboratory data were collected before and six months after tadalafil initiation.ResultsOver the study period, 154 children with a median age of 1.0 (range 0.0-6.9) years were treated with tadalafil therapy. Of these, 39 (25.3%) were in group 1 (PAH), 79 (51.3%) were in group 3 (lung disease), and 33 (21.4%) were in group 5 (pulmonary hypertensive vascular disease). The median initial dose of tadalafil was 1.0 mg/kg once daily. Eleven (7.1%) patients in the cohort were established on tadalafil therapy de novo. The suspension formulation was necessary for 103 (66.9%) patients due to an inability to take enteral tablets and for 49 (31.8%) due to a need for feeding via gastric or jejunal tubes. We observed a statistically significant increase in tricuspid annular plane systolic excursion as well as significant decreases in right-ventricular systolic pressure and NT-proBNP. Tadalafil therapy was well tolerated over the six-month period: at six months, no adverse effects were reported aside from gastrointestinal disturbances by 2 (1.3%) patients.ConclusionTadalafil, a long-acting PDE5 inhibitor, when administered in a suspension formulation, has a safe and tolerable adverse effect profile. Following six months of therapy, our cohort showed improvements in clinical parameters, echocardiographic measurements, and laboratory results. Patient compliance was good and adverse effects were rare, minor, and manageable with nonpharmacological means.